Comparing neo and traditional banking efficiency: a three-stage DEA analysis in Indonesia - Daffa Rizqi Prayudya; Ihsanul Ikhwan; Taufik Nugroho; Ratu Ghifa Nazila Ramdiania (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to compare neo and traditional banking efficiency, as well as the driving factors. A sample of five Indonesian neo banks and five traditional banks from Q1 2021 to Q4 2023 is employed. The method uses a three-stage method using an intermediation approach, incorporating data envelopment analysis (DEA), DEA windows analysis (DEWA), and Tobit regression. The DEA results indicate that traditional banks demonstrate higher efficiency compared to neo banks. PT Bank Tabungan Negara Tbk and PT Bank Rakyat Indonesia Tbk stand out as the most efficient, while PT. Bank Jago Tbk, a neo bank, records the lowest efficiency score. DEWA demonstrates the stability of efficiency levels over the observed period. Tobit regression analysis further reinforces that neo banks are less efficient than traditional banks. Traditional banks, with their refined operations reputations, attract more deposits and loans, resulting in higher efficiency. In contrast, neo banks face challenges due to their steep learning curve and lack of established customer trust. Revamped regulations and strategic partnerships are essential to expanding lending channels for neo banks, potentially through collaborations with traditional banks or mergers.